Stress-Strain Relationship of Ca(OH)2-Activated Hwangtoh Concrete - Keun-Hyeok Yang; Ju-Hyun Mun; Hey-Zoo Hwang (The Scientific World Journal)
This study examined the stress-strain behavior of 10 calcium hydroxide (Ca(OH)2)-activated Hwangtoh concrete mixes. The volumetric ratio of the coarse aggregate (Vagg) and the water-to-binder (W/B) ratio were selected as the main test variables. Two W/B ratios (25% and 40%) were used and the value of Vagg varied between 0% and 40.0%, and 0% and 46.5% for W/B ratios of 25% and 40%, respectively. The test results demonstrated that the slope of the ascending branch of the stress-strain curve of Ca(OH)2-activated Hwangtoh concrete was smaller, and it displayed a steeper drop in stress in the descending branch, compared with those of ordinary Portland cement (OPC) concrete with the same compressive strength. This trend was more pronounced with the increase in the W/B ratio and decrease in Vagg. Based on the experimental observations, a simple and rational stress-strain model was established mathematically. Furthermore, the modulus of elasticity and strain at peak stress of the Ca(OH)2-activated Hwangtoh concrete were formulated as a function of its compressive strength and Vagg. The proposed stress-strain model predicted the actual behavior accurately, whereas the previous models formulated using OPC concrete data were limited in their applicability to Ca(OH)2-activated Hwangtoh concrete.